أثر الاتفاق النووي الإيراني على العلاقات العربية – الإيرانية - الأحمد, محمد; موسى, علي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research provides an analysis of the crisis of the Iranian nuclear file, which was a constructive factor in international relations, especially after the US occupation of Iraq in 2003, and examines the reasons that led the Iranian decision maker to adhere to the possession of nuclear technology for peaceful purposes, despite the threats of America and " Which has reached the threat of military war on Iran. The research shows the long and arduous negotiations between Iran and the five plus one countries, which led to a historic agreement signed in the Swiss city of Lausanne in 2015. Arabic And "Israel" on this agreement, where the parties considered that the agreement will increase Iranian interference in the affairs of the Arab region, and will not prevent them from the continuing threat to the security of the countries and peoples of this region, while examining the impact of the signing of this agreement on Iran and the crises of the Arab region, With the national state in Syria, and is a main supporter of the resistance in both Lebanon and Palestine, and envisions the Arab-Iranian relations after this agreement, which may establish a constructive dialogue that achieves an Arab-Iranian partnership and eliminates the outstanding problems between them. يقدم البحث تحليلاً عن أزمة الملف النووي الإيراني التي شكلت عاملاً بناءً في العلاقات الدولية, وعلى الأخص بعد الاحتلال الأمريكي للعراق عام 2003, ويبحث في الأسباب التي دفعت صانع القرار الإيراني إلى التمسك بامتلاك التكنولوجيا النووية للأغراض السلمية, على الرغم من التهديدات الأمريكية و"الإسرائيلية" التي وصلت إلى التهديد بشن حرب عسكرية على إيران, ويبين البحث مسار المفاوضات الطويلة والشاقة بين إيران من جهة ودول (الخمسة + واحد) من جهة أخرى, والتي أفضت إلى اتفاق تاريخي تمّ توقيعه في مدينة لوزان السويسرية عام 2015, ويحلل البحث أسباب اعتراض دول الخليج العربية و"إسرائيل" على هذا الاتفاق, حيث اعتبر الطرفان أن الاتفاق سيزيد من التدخل الإيراني في شؤون المنطقة العربية, ولن يمنعها من التهديد المستمر لأمن دول وشعوب هذه المنطقة, مع دراسة أثر توقيع هذا الاتفاق على إيران وعلى أزمات المنطقة العربية, وخاصةً أن إيران تقف مع الدولة الوطنية في سوريا, وتعدّ داعماً أساسياً للمقاومة في كل من لبنان وفلسطين, ويستشرف العلاقات العربية-الإيرانية بعد هذا الاتفاق الذي قد يؤسس لحوارٍ بناء يحقق شراكةً عربية-إيرانية, ويزيل المشاكل العالقة بينهما.